Regulation of international trade and services - Sheremet, Y. D. (ТДАТУ, 2019)
Currently, trade barriers in the international services market are powerful tools and are mainly used to support national security, public and private monopoly status, for example, immigration, licensing services. Therefore, work on liberalizing the global service markets has been started within the WTO, as it remains the most protected area today owing to the participating States.
Keywords: international trade; services market; service; International trade